Improvement of Time Complexity on Pattern Matching using One -Time Look Indexing and Data Preprocessing - Hrushikesava Raju, S; Nagabhushana Rao, M (International Journal of Computer Sciences and Engineering, 2025)
There are various pattern matching algorithms which take more comparisons in finding a given pattern in the text and are static and restrictive. In order to search pattern or substring of a pattern in the text with less number of comparisons, a general data mining technique is used called data preprocessing which named as D-PM using DP with help of one time look indexing method. The D-PM using DP finds given pattern or substring of given pattern in the text in less time and the time complexity involved is less than existing pattern matching algorithms. The new Pattern Matching Algorithm with data preprocessing (D-PM using DP) proposes Pattern Matching with dynamic search behavior and makes users should have flexibility in searching.